Development of Wellness Culture through corrective gymnastics - Darinka Ignatova (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. Immobility leads to a decrease in the adaptive functions of the body, which is expressed in a weakening of the immune system and disorders in the psycho-emotional state. In addition, it harms the musculoskeletal system. The aim is to establish the influence of corrective spinal gymnastics on the development of the wellness culture, through optimal motor load in the tracked age period.